Study of maternal serum lipid profile and apolipoprotein a levels and its correlation with fetal growth restriction - Devi, Akoijam Tamphasana; Yadav, Reena; Yadav, Amita; Singh, Yanglem Ajitkumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: This study was aimed to estimate maternal serum lipid profile and apolipoprotein A levels in pregnancies complicated with FGR and to compare the levels with the levels in normal pregnancies. Methods: A prospective observational study was conducted in Lady Hardinge Medical College, New Delhi, in a study group consisting of 30 pregnant women at gestation 32-34 weeks with ultrasound diagnosed FGR and control group consisting of 30 age and gestation matched uncomplicated pregnant women. Maternal serum lipid profile and apolipoprotein A levels were measured and compared between the two groups. Results: Total serum cholesterol, triglyceride, LDL-cholesterol, VLDL-cholesterol and Apolipoprotein A were significantly lower in FGR group compared to normal controls. Mean±SD of total cholesterol was found to be 199.17±49.06 mg/dl in cases and 244.10±53.17 mg/dl in controls. Mean±SD of triglyceride was 200.53±60.25 mg/dl in cases compared to 304.13±69.12 mg/dl in controls. Mean±SD of LDL-Cholesterol was 98.19±37.91 mg/dl in cases and 127.07±47.84 mg/dl in controls. Mean±SD of VLDL-cholesterol was 40.11±12.05 mg/dl in cases and 60.83±13.82 mg/dl in controls. Mean±SD of Apolipoprotein A was 147.71±16.40 mg/dl in cases compared to 163.30±16.07 mg/dl in controls. HDL-cholesterol did not change significantly as its mean±SD was 60.87±15.18 mg/dl in FGR group and 56.20±16.07 mg/dl in control group. Conclusions: The decreased levels of total cholesterol, triglyceride, LDL-cholesterol, VLDL-cholesterol and apolipoprotein A levels may be used as biochemical marker for detection of FGR.